GEOFÍSICA APLICADA A LA EVALUACIÓN DE LA VULNERABILIDAD A LA CONTAMINACIÓN EN ZONAS RURALES - Sainato, Claudia Mabel; Losinno, Beatriz Norma; Galindo, Griselda; Landini, Ana Maria; Fazio, Ana Maria (Águas Subterrâneas, 2006)